2022
DOI: 10.1111/1467-8551.12602
|View full text |Cite
|
Sign up to set email alerts
|

How Does Firm‐Specific Investor Sentiment Affect the Value of Corporate Cash Holdings?

Abstract: We document a positive relation between firm‐specific investor sentiment (FSIS) and the value of cash. We also show that FSIS has a stronger positive effect on the value of cash than the value of other types of assets, suggesting that our finding is not a simple reflection of firm‐level overvaluation. Our finding is robust to alternative measures of change in cash, different cash regimes, FSIS measured by order imbalance, news sentiment and the tone of earnings conference call transcripts and controlling for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 97 publications
1
6
0
Order By: Relevance
“…Similarly, Li and Li (2021) deepen the understanding of how firm-specific investor sentiment behaves in the Chinese stock market, using overnight and over-weekend stock returns as proxies. Similar studies were conducted in Korean market (Seok et al, 2019;Kim et al, 2021), and even in US stock market (Guo et al, 2023).…”
Section: Investor Sentiment and Earnings Managementsupporting
confidence: 71%
“…Similarly, Li and Li (2021) deepen the understanding of how firm-specific investor sentiment behaves in the Chinese stock market, using overnight and over-weekend stock returns as proxies. Similar studies were conducted in Korean market (Seok et al, 2019;Kim et al, 2021), and even in US stock market (Guo et al, 2023).…”
Section: Investor Sentiment and Earnings Managementsupporting
confidence: 71%
“…In a related study, Ward et al (2018) found that monitoring by economically motivated institutional investors enhances the value of cash holdings. Additionally, Guo et al (2023) show that firm-specific investors’ sentiments have a strong relationship with the value of cash holdings. Moreover, effective oversight of managerial self-serving behaviors may positively affect investors’ sentiments about the value of excess cash holdings (Ilyas et al , 2022), which suggests that minority investors anticipate cash holdings at a premium if corporate governance is stronger.…”
Section: Related Literature and Hypotheses Developmentmentioning
confidence: 97%
“…We contribute to this discussion by examining the influence of irrational investor behaviour in financial markets; this issue is of importance to management scholars and corporate managers, as the functioning of these markets is known to have real efficiency consequences via corporate behaviour and managerial decision-making (Bond et al, 2012;Dow et al, 2017;Xiao, 2020). How markets function impacts managerial decisions, including initial purchase orders (IPOs; Latham and Braun, 2010), mergers and acquisitions (Bozos et al, 2014), payout policies (Polk and Sapienza, 2009), share repurchases (Babenko et al, 2012;D'Mello and Shroff, 2000;Dittmar and Field, 2015), equity issuance (Baker and Wurgler, 2002) and cash holdings (Guo et al, 2022). Hence, an understanding of stock market irrationality can lead to an understanding of corporate structures and behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…How markets function impacts managerial decisions, including initial purchase orders (IPOs; Latham and Braun, 2010), mergers and acquisitions (Bozos et al. , 2014), payout policies (Polk and Sapienza, 2009), share repurchases (Babenko et al , 2012; D'Mello and Shroff, 2000; Dittmar and Field, 2015), equity issuance (Baker and Wurgler, 2002) and cash holdings (Guo et al , 2022). Hence, an understanding of stock market irrationality can lead to an understanding of corporate structures and behaviours.…”
Section: Introductionmentioning
confidence: 99%